Dampak Rotasi Tanaman Terhadap Kesuburan Tanah dan Produksi Tanaman di Lahan Pertanian Subur Tropis - Ngabito, Afrianti; Gaib, Yulia Oliviana (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of crop rotation on soil fertility and productivity of agricultural products in the fertile tropical land of the North Gorontalo region. The method used was a field experiment with a random group design (RAK), using a combination of rotation of maize, peanuts, and sweet potatoes during the two growing seasons. The parameters observed included soil pH, C-organic content, macronutrients (N, P, K), soil microorganism activity, and main crop yields. The results of the study show that the crop rotation system has a significant influence on improving soil quality and production yields compared to monoculture systems. Rotations involving leguminosa plants specifically increase soil nitrogen levels and microbial activity, as well as stabilize soil pH. Meanwhile, corn crop yields increased by 20% on rotated land compared to non-rotational land. This study concludes that crop rotation is an effective and sustainable strategy in maintaining and increasing the fertility of fertile tropical soils. The novelty of the research lies in the application of local plant-based rotation patterns in areas that have not been widely studied scientifically. These findings are expected to be a reference in the development of regenerative agricultural systems that are adaptive to tropical ecosystem conditions.